2001
DOI: 10.1007/s100960100593
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial DNA and rRNA Amplification Assays for Assessment of Treatment Outcome in Pulmonary Tuberculosis Patients

Abstract: To evaluate the clinical utility of the DNA and RNA amplification assays in monitoring the efficacy of tuberculosis treatment, 416 sputum specimens collected from 15 smear-positive tuberculosis patients during and after treatment were tested for the presence of Mycobacterium tuberculosis by microscopy, culture, polymerase chain reaction (Cobas Amplicor Mycobacterium Tuberculosis Test; Roche, Switzerland) and AMTDT 2 (Amplified Mycobacterium Tuberculosis Direct Test; Gen Probe, USA). All patients were cured, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…More recently, an enhanced MTD has also been approved for smear-negative respiratory specimens of suspect patients [89]. Several studies have evaluated both tests for the detection of M. tuberculosis in clinical samples [90]. Compared with culture and the clinical status, these methods have a high sensitivity and specificity in smear-positive specimens, but lower values are obtained in smear-negative specimens precluding their use as a screen to rule out the disease.…”
Section: Nucleic Acid Amplification Methodsmentioning
confidence: 99%
“…More recently, an enhanced MTD has also been approved for smear-negative respiratory specimens of suspect patients [89]. Several studies have evaluated both tests for the detection of M. tuberculosis in clinical samples [90]. Compared with culture and the clinical status, these methods have a high sensitivity and specificity in smear-positive specimens, but lower values are obtained in smear-negative specimens precluding their use as a screen to rule out the disease.…”
Section: Nucleic Acid Amplification Methodsmentioning
confidence: 99%
“…The laboratory performance of both commercial and in house TB PCR in the diagnosis of tuberculosis has been extensively evaluated. [1][2][3][4][5][6][7][8][9] However, there are few data on the ''in use'' evaluation of TB PCR as a tool for clinical decision making in the management of tuberculosis.…”
mentioning
confidence: 99%
“…Some studies have found PCR positive results from patients with only a tuberculosis infection or a past history of tuberculosis (Yuen et al 1993, Rajalahti et al 2001. In the present study, there was only one BACTEC ® 12B vial that was PCR positive for MTBC but culture positive for NTM.…”
Section: Discussionmentioning
confidence: 38%